(untitled) (MAUSAM, 1952)
In the India Meteorological Department it is a long standing practiceto describe the occurrence of rainfall over the various meteorological divisions of the country, in terms of widespread, local and fewfalls according to the distribution of rainfall. The same terms have also been in use in forecasts of rainfall to indicate the expected distribution of rainfall. With an idea of obtaining the number of occasions of the different types of distribution of rainfall in different parts of the Country, statistics have been compiled in respect of all the meteorological subdivisions of pre-partition India from ten years ’data of the years 1930-39, published in Indian Daily Weather Reports. Tables are given showing for each division the average number of days of widespread, local and few falls together with the highest and lowest number of days under each category. The number of days of rainfall (sum of the days of all the three types of rainfall distribution) and the number of days of widespread rainfall for each meteorological subdivision in different months of the year have been discussed. With regard to the number of days of rainfall of the meteorological subdivisions it is seen that some divisions show only one peak during the year while others have two peaks. The peak which all the divisions have is due to the southwest monsoon and the other is practically due to the western disturbances. The peak observed during the month of active western disturbances is noticeable in the south up to the Madras Deccan, showing that the secondary or tertiary effects of the western disturbances are occasionally produced so far South as the Madras Deccan.